Penggunaan Bahasa Melalui Copywriting Instagram Sebagai Media Pemasaran Wisata Alam Kebontunggul - Sabila, Dinda; Maharani, Angelia Brigita (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
Tourism promotion often utilizes advertising media that employs language and writing as communication tools to convey ideas and offer services. In this context, the community service activities carried out by students of Universitas 17 Agustus 1945 Surabaya in Kebontunggul, Mojokerto, aim to help develop marketing strategies for the natural tourist destination of Lembah Mbencirang. These activities focus on empowering the local marketing team through training in using social media, particularly Instagram, as a platform to attract the attention of potential visitors. One of the main approaches used is copywriting, a persuasive writing technique designed to influence the audience and encourage interaction and visits to the tourist destination. The results of these activities are expected to enhance the appeal of Lembah Mbencirang as a tourist destination, attracting potential visitors to enjoy its various services, such as outbound activities, family gatherings, camping grounds, and swimming pools, while also expanding marketing reach through more effective social media use. Through effective copywriting strategies, students strive to increase the appeal of the tourist destination. This program not only aims to increase tourist visits but also empowers the local community to manage and optimize their area's tourism potential, thereby positively impacting the local economy and the sustainability of the tourist destination.